Anti‐VEGF DNA‐based aptamers in cancer therapeutics and diagnostics. Issue 1 (10th October 2020) - Riccardi, Claudia; Napolitano, Ettore; Platella, Chiara; Musumeci, Domenica; Melone, Mariarosa A. B.; Montesarchio, Daniela
Abstract: The vascular endothelial growth factor (VEGF) family and its receptors play fundamental roles not only in physiological but also in pathological angiogenesis, characteristic of cancer progression. Aiming at finding putative treatments for several malignancies, various small molecules, antibodies, or protein‐based drugs have been evaluated in vitro and in vivo as VEGF inhibitors, providing efficient agents approved for clinical use. Due to the high clinical importance of VEGF, also a great number of anti‐VEGF nucleic acid‐based aptamers—that is, oligonucleotides able to bind with high affinity and specificity a selected biological target—have been developed as promising agents in anticancer strategies. Notable research efforts have been made in optimization processes of the identified aptamers, searching for increased target affinity and/or bioactivity by exploring structural analogues of the lead compounds. This review is focused on recent studies devoted to the development of DNA‐based aptamers designed to target VEGF. Their therapeutic potential as well as their significance in the construction of highly selective biosensors is here discussed.